2020
DOI: 10.1016/j.jcrc.2020.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate prophylactic effect of low-molecular weight heparin in critically ill COVID-19 patients

Abstract: Purpose The aim of this study was to investigate potential markers of coagulopathy and the effects of thromboprophylaxis with low-molecular-weight heparin (LMWH) on thromboelastography (TEG) and anti-factor Xa in critically ill COVID-19 patients. Material and Methods We conducted a prospective study in 31 consecutive adult intensive care unit (ICU) patients. TEG with and without heparinase and anti-factor Xa analysis were performed. Standard thromboprophylaxis was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…In this study, all patients had MA ≥ 65 mm, and at the late timepoint, 3 out of 4 non-recovering patients had MA ≥ 77 mm (Table 2). Increased MA has previously been reported in critically ill COVID-19 patients ( 5, 39, 40 ). Platelet count and D-dimer were not different between recovering and non-recovering patients, but both were significantly increased compared to healthy controls (Table 2).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this study, all patients had MA ≥ 65 mm, and at the late timepoint, 3 out of 4 non-recovering patients had MA ≥ 77 mm (Table 2). Increased MA has previously been reported in critically ill COVID-19 patients ( 5, 39, 40 ). Platelet count and D-dimer were not different between recovering and non-recovering patients, but both were significantly increased compared to healthy controls (Table 2).…”
Section: Discussionmentioning
confidence: 60%
“…SARS-CoV-2 infection may be paucisymptomatic, or lead to coronavirus disease-2019 (COVID-19), which has a wide range of symptoms and may cause severe illness, in particular in individuals with other cardiovascular risk factors ( 1 ). Thrombotic and thromboembolic disease has emerged as a major COVID-19 complication despite routine thrombosis prophylaxis now being standard of care ( 2-5 ). Microthrombosis has been suggested to contribute to both respiratory failure and neurological complications ( 6, 7 ), and activation of the coagulation system indicates a poor prognosis among COVID-19 patients in intensive care ( 1, 7-9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced fibrinolytic activity was also observed in patients with COVID-19, with all studies reporting LY30 less than 1%, including three which showed complete fibrinolytic shutdown (LY30 of 0%) [ 18 , 23 , 25 ]. A shortened R-time of less than 5 min was observed in patients from four studies [ 18 , 20 , 22 , 26 ], indicating a shorter time to clot formation in hypercoagulable patients, although the R-value was within the range of normal in most studies ( Figure 4 ), implying that the change in R-time is less consistent than the increased MA [ 5 , 14 , 15 , 19 ] and fibrinolytic shutdown in the characterization of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…VETs were performed using ROTEM (25 studies), TEG (15 studies), Quantra (two prospective studies [66,67]) and ClotPro (one retrospective study [24] and one case report [68]); no study compared two devices. Among articles reporting data about TEG, four were prospective studies [52,[59][60][61], ten were retrospective studies [51,[53][54][55][56][57][58][62][63][64], and one was a case report [65]. Among articles dealing with ROTEM, thirteen were prospective studies [28][29][30][31][32][39][40][41][42][43][44][45][46], seven were retrospective studies [27,[33][34][35][36]48,49], one was a cross-sectional study [47], and four were case reports [26,37,38,50].…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…Testing was carried out either on admission or within the following days, but the timing of blood collection for VET was specified only for 29 studies [24,26,27,[29][30][31]33,[35][36][37][38]41,[43][44][45][46][47][48]50,53,[55][56][57][58][59][65][66][67]. In some studies, the measurements were repeated during the patientʹs stay, either because of a pre-established protocol [26,27,29,45,53,59,60,67] or because of the occurrence of a thromboembolic event [65,68]. Number of VETs performed during a patient's stay ranged from 1 to 5 [29].…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%